ENVIRO-HIRLAM: on-line coupled modelling of urban meteorology and air pollution - A. Baklanov; U. Korsholm; A. Mahura; C. Petersen; A. Gross (Advances in Science and Research, 2008)
The strategy of new generation integrated Meso-Meteorological (MetM) and Atmospheric Chemical Transport (ACT) models for predicting atmospheric composition, meteorology and climate change is discussed for the Enviro-HIRLAM (HIgh Resolution Limited Area Model) integrated system. Current progress in the Enviro-HIRLAM system development and its urban on-line coupled modelling applications is considered. Results of several sensitivity studies of the urban effects (urban albedo and roughness, anthropogenic heat flux, heat island, and urban aerosols) on meteorology and air pollution at different scales are presented. Several sensitivity tests of the off-line versus on-line coupling of MetM and ACT models in Enviro-HIRLAM as well as their verification versus the ETEX experiment are considered and results are discussed.